2022
DOI: 10.1177/17470218221102922
|View full text |Cite
|
Sign up to set email alerts
|

Testing links between pain-related biases in visual attention and recognition memory: An eye-tracking study based on an impending pain paradigm

Abstract: Although separate lines of research have evaluated pain-related biases in attention or memory, laboratory studies examining links between attention and memory for pain-related information have received little consideration. In this eye-tracking experiment, we assessed relations between pain-related attention biases (ABs) and recognition memory biases (MBs) among 122 pain-free adults randomly assigned to impending pain (n = 59) versus impending touch (n = 63) conditions wherein offsets of trials that included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…A recent study reported that pain cueing to personal potential discomfort led to more attention and was subsequently identified more accurately ( Zuo et al, 2022 ). It suggests that women who have experienced menstrual pain, especially if they are suffering from menstrual pain, will pay more attention to the painful period when they are about to have their period, due to the unpleasant memories of their previous periods.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that pain cueing to personal potential discomfort led to more attention and was subsequently identified more accurately ( Zuo et al, 2022 ). It suggests that women who have experienced menstrual pain, especially if they are suffering from menstrual pain, will pay more attention to the painful period when they are about to have their period, due to the unpleasant memories of their previous periods.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, participants mostly gazed at pain ratings that corresponded to the pain ratings their later chose (i.e., Median pain rating was 7) and to critical Pain Management -From Acute to Chronic and Beyond elements in the instructions. Regarding the latter, visual attention tends to be maintained on pain cues that signal potential personal discomfort [56]. It would therefore be of interest to assess in future studies whether patients tended to gaze more at verbal stimuli due to their content (e.g., "unbearable pain," which constitutes the rightward anchor) and whether this correlates with their pain ratings.…”
Section: Relative Gaze Duration Heatmap; Visualizing the Proportion O...mentioning
confidence: 99%